Effects of Postgraduate Training Program on the Professional Approach to Sexual Assault Cases - Yavuz, Mehmet Fatih (The Bulletin of Legal Medicine, 2001)
The most effective way in eliminating a problem is first to put it forward with all aspects. Along with other factors, the negative approach of the related professions such as police, attorneys and judges stemming from their false beliefs is an important cause in low reporting ratios of sexual assaults. Educational programs where the real information is gathered seems to be the most important place to prevent the biased and unobjective approaches. The aim of the study is to evaluate the effects of sexual assault training program on the professional approach to sexual assault events. Thirty graduate students having different professional backgrounds such as judges, attorneys, police and psychologists, who took the “sexual crimes” course given by the author for 28 hours in 14 weeks voluntarily participated in the study. The observed differences in the consideration of the matter before and after the education are defined to be positive. As a consequence, post graduate sexual assault training programs received by the related professions will have positive impact on objective approach to sexual assault cases.Key words: Sexual assault, date rape, false believes, education
Keywords: sexual assault; date rape; false believes; education